Endovascular treatment versus open surgery for iliac artery aneurysms: a systematic review and meta-analysis - Machado, Marta; Coelho, Andreia; Peixoto, João; Fernandes, Luís; Basílio, Francisco; Carvalho, Patrícia; Brandão, Pedro; Canedo, Alexandra (Angiologia e Cirurgia Vascular, 2024)
INTRODUCTION: Due to their relative rarity, the natural history of iliac artery aneurysms and treatment outcomes are poorly understood. However, IAA treatment has evolved, and nowadays, there are a variety of open surgery, endovascular therapy, and hybrid options. This study aimed to compare the outcomes of endovascular treatment versus open surgery for patients with iliac artery aneurysms. METHODS: A systematic review was performed according to the PRISMA statement. An online search was conducted using the Medline database from January 2014 to January 31st, 2023. Only original articles in English or Portuguese, reporting on a minimum of 5 cases, were considered. Studies were included if reporting at least one of the following outcomes: peri-operative complications, length of stay (LS), and 30-day mortality. The software Review Manager 5.4 was used for data analysis. RESULTS: The database search identified 418 articles, of which 413 records were excluded by screening by title/ abstract, and five were read in full and subsequently included. A total of 1837 patients were included. Open surgery was performed in 29.02% (442/1523) and endovascular in 70.58% (1075/1523). More than half of endovascular cases included internal iliac artery preservation techniques (iliac branch design grafts). Patients undergoing endovascular treatment were significantly older (mean difference [MD]: 5.49, 95% confidence interval [CI]: 2.34 to 8.65) and more likely to have congestive heart failure (odd ratio [OR]: 3.74, 95% CI: 1.24-11.27). On the other hand, patients undergoing open surgery were more often smokers (OR: 0.59, 95% CI: 0.42-0.82). The primary outcome - 30-day mortality - was significantly higher for open surgery (OR 0.34, 95% CI 0.19-0.61). Considering other peri-operative outcomes, patients undergoing open surgery presented with longer length of hospital stay (MD: -4.68, 95% CI: -6.43 to -2.92), higher risk of surgical wound infection (OR: 0.31, 95% CI: 0.10- 0.94), renal failure (OR: 0.37, 95% CI: 0.18-0.75) and respiratory infection (OR: 0.19, 95% CI: 0.11-0.33). No significant differences regarding buttock claudication and leg and bowel ischemia were found. The 30-day reintervention rates weren ́t significantly different for open and endovascular surgery (OR 0.83, 95% CI 0.33-2.1). CONCLUSION: Endovascular treatment of iliac artery aneurysms can reduce 30-day mortality, peri-operative complications and length of hospitalization. No differences were identified regarding 30-day reintervention rates. Consequently, endovascular treatment has gained preference over open surgery as the initial approach for patients with suitable anatomy. No other meta-analysis in the literature compares the results of open surgery and endovascular treatment, particularly the results of new endovascular techniques (iliac branch design grafts). Comparing long-term reintervention rates will be essential in the future.